Education is soul deep - Abd Razak, Dzulkifli (2007)
HARRY Lewis, a professor and longtime dean of Harvard College at Harvard University, wrote an analysis of the university last year. On reading his book, Excellence Without a Soul: How a Great University Forgot Education, one gets the impression that something is amiss in undergraduate education at the university. Lewis implies that the university, indeed others in the US, too, is losing its "soul" as it becomes more and more consumerdriven. Increasingly, universities seem to cater to students' desires, instead of shaping their character as citizens. Arguably, academic achievement alone is not sufficient to imbue good citizenship. Thus, it is alleged that there is a decline in American society because its elite universities — on which so much of the future depends—have forgotten about education.